Perlindungan Hukum Bagi Konsumen Kesehatan Yang Mengalami Malapraktik - Saragih, Alexandra Exelsia; Arifin, Azzahra; Nalom, Hizkia; Azzahra, Nabila Adifia; Zalfa, Nabila (Media Hukum Indonesia (MHI), 2024)
The main aim of this research is to find out what the law is for health consumers who experience malpractice and to find out what are the obstacles to the rights of health consumers who experience malpractice. This is very important to explain so that anyone knows about legal protection from malpractice cases and can find out the causes and effects of these cases. The research method used in this article is a normative legal research method which focuses on positive law inventory, legal principles and doctrine, legal discovery in cases in concreto, legal systematics, level of synchronization, legal comparison and legal history. The conclusion of this research is that in terms of proving malpractice, consumers must be able to prove that the injuries experienced by consumers/patients are the result of violations committed by health workers.